Maqasid Syari'ah Sebagai Koridor Pengelolaan Perbankan Syariah - Moh Nasuka; Subaidi Subaidi (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2017)
A wave of vanity of modernity and global industrialization has sneaked into the joints of human life. So in turn, contemporary Islamic thought with all its tools, including the methodology of uṣūl al-fiqh and qawā'id al-fiqhiyyah which has been one of the references and the cornerstone of Islamic banking practice, should mimamorphose with the passage of time and relitas. In other words, it is necessary to incorporate revelation into scientific research in order to free Muslim scholars from the coercion of Western epistemology or to adopt the conventional economic and financial parktics without considering all the risks. This is a great work to be done in order to build Islamic self-image (self image of Islam) in the midst of modern life that is always changing and developing. In this regard, Maqāṣid Syar''ah is a relevant corridor as the basis for system development, practice, and even Islamic banking products in the multidimensional era. In relation to the above issues, this study will describe the values ​​of Maqāṣid Syarī'ah as the corridors of the management of today's Islamic banking institutions. These values ​​can provide protection to customers to be preserved in various aspects of life, including: his religion, his mind, his soul, his descendants and his possessions. This paper is expected to contribute theoretically in the field of Islamic economics and can be used as a reference management of sharia financial institutions and especially for Islamic banking institutions.